HUBUNGAN UNDANG-UNDANG NOMOR 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS DENGAN PERAN PERUSAHAAN DALAM PELAYANAN MASYARAKAT - Supendi; Pandri Zulfikar; Asri Cahyadi (Berajah Journal, 2026)
Law Number 40 of 2007 concerning Limited Liability Companies (LLC Law) serves as the fundamental legal framework governing the existence and operations of limited liability companies in Indonesia. Among various provisions regulated in the LLC Law, Article 74 concerning Social and Environmental Responsibility (TJSL) or Corporate Social Responsibility (CSR) represents a significant legal instrument in encouraging companies to play an active role in community service. This research aims to analyze the legal relationship between the provisions of the LLC Law and the role of companies in community service, examine the juridical implications of TJSL obligations, and evaluate the effectiveness of implementing these provisions in practice. The research method used is normative legal research with statutory, conceptual, and comparative approaches. The results indicate that the LLC Law has provided a strong legal basis for companies to carry out community service through TJSL, but there are normative inconsistencies between the mandatory nature of TJSL obligations in Article 74 paragraph (1) and the voluntary commitment definition of CSR in Article 1 number 3. Furthermore, the weakness of sanctions not specifically regulated in the LLC Law reduces the effectiveness of law enforcement against companies that fail to fulfill their obligations. This study recommends the need for harmonization of LLC Law provisions with their implementing regulations to strengthen the role of companies in community service.